Conceptual development of a compact unglazed solar thermal facade (STF) for building integration - Shen, Jingchun; Zhang, Xingxing; Yang, Tong; Tang, Llewellyn; Wu, Yupeng; Jin, Ruoyu; Pan, Song; Wu, Jinshun; Xu, Peng (Elsevier, 2016)
This research aims to develop an initiative modular unglazed Solar Thermal Facade (STF) concept initially for hot water generation to facilitate the integration of solar energy with buildings. The new STF concept is simple structure, low cost, and aesthetically appealing with easy installation but is expected to achieve the equivalent thermal efficiency as the conventional STFs. It delivered alternative design in terms of material, colour, texture, shape, size, architectural design, installation method, array connection, hypothetical system application, and solar coverage. Two common design variants i.e. (a) the STF cladding system and (b) the prefabricated STF wall system were described respectively for existing and new low-rise building typologies. Interaction of inclination, orientation, and insolation were discussed for the optimum STF position on the building. Four currently available methods for installation of such STF with buildings were summarized and three typical array connection methods were identified. The decentralized connection was recommended for different types of STF hot water systems. It is customary to design for a solar coverage of 50 to 60 percent for water heating in detached houses; in apartment buildings 30 to 40 percent are more commonly assumed. The concept design in this paper hereby illustrates the precedence for the hypothetical function by the creation of new ideas and also forms up the physical structure or operating principle for the investigations in near future.